1923 N.Y. Laws 140-41 - (:unkn) unknown (My University, 1923)
An Act to Amend the Conservation Law in Relation to Aliens, ch. 110, § 2: Prohibited noncitizens from owning or possessing any shotgun or rifle without a special license.
Keywords: POSSESSION - DANGEROUS PERSONS